2007
DOI: 10.4172/plastic-surgery.1000500
|View full text |Cite
|
Sign up to set email alerts
|

A bilobed groin flap for coverage of traumatic injury to both the volar and dorsal hand surfaces

Abstract: BACKGROUND: There are many methods available for coverage of both the volar and dorsal hand surfaces in traumatic injury. All of these surgical procedures allow for ample coverage of the defect, but have the major drawback of needing multiple donor sites. In the present report, a case of a complex crush injury to the hand in which both volar and dorsal surfaces received traumatic injury is presented. A bilobed groin flap pedicled on the superficial circumflex iliac artery was fashioned to cover the entire defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…However, this flap will not cover extensive dorsal and volar hand defects, particularly without time-consuming delay procedures or tissue expansion [8]. Extensive tissue loss warrants multiple-flap reconstruction [9,10,12,14,15,17,18]. The pedicled ALT flap was not described in hand reconstruction before this decade [21,23].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this flap will not cover extensive dorsal and volar hand defects, particularly without time-consuming delay procedures or tissue expansion [8]. Extensive tissue loss warrants multiple-flap reconstruction [9,10,12,14,15,17,18]. The pedicled ALT flap was not described in hand reconstruction before this decade [21,23].…”
Section: Discussionmentioning
confidence: 97%
“…However, they may not cover extensive defects that involve the dorsal and palmar hand, particularly without a time-consuming delay procedure or tissue expansion [8]. Paired groin and abdomen flaps have been described since the 1970s [2,5,[9][10][11][12][13][14][15][16][17][18], which are better suited to extensive and three-dimensional wounds.…”
Section: Introductionmentioning
confidence: 99%
“…The groin flap, supplied by the superficial circumflex iliac artery system, was defined by McGregor and Jackson in 1972. 1,[9][10][11][12] Free groin flap was first used in 1973 by Daniel and Taylor. 13 Pedicled groin flap is frequently used in the same hand and upper extremity defects.…”
Section: Discussionmentioning
confidence: 99%
“…Bilobed groin flap was described in correcting the hand in Apert syndrome and in closing the defect that formed after opening the thumb contracture. 1,20,21 Further, bilobed groin flap is described in the literature for the reconstruction of defects secondary to trauma on the dorsal and volar surfaces of the hand. 1 Tan et al 5 reported reconstructing a defect spanning both of the two digits on the second web space with a winged groin flap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation